Platelet count splenic diameter ratio as predictor for esophageal varices in patients with cirrhosis: a diagnostic evaluation study - Mathew, Sunil; Chacko, Sachin; Philip, Tomy; Sharma, R. N.; Binub, Kanniyan (International Journal of Research in Medical Sciences, 2019)
Background: Esophageal variceal bleeding is one among the common complication of cirrhosis which is fatal. Latest studies are focusing more on using non-invasive techniques to classify cirrhotic patients according to their risk of having varices. The platelet count-splenic diameter ratio is considered as one such parameter and is used in predicting esophageal varices in patients with cirrhosis. Objectives of the study was to assess the utility of platelet count-splenic diameter ratio as a useful non- invasive parameter in predicting the presence/ absence /size of esophageal varices in patients with cirrhosis. Methods: Diagnostic evaluation study was done in a tertiary hospital of Kerala state India. 93 adults above the age of 18 yrs with diagnosis of cirrhosis was selected and detailed history, physical, systemic examination and imaging was done. The degree of correlation between platelet count-splenic size ratio and the presence/absence/size of esophageal varices was studied along with its utility as an independent non- invasive marker. Frequency was expressed in percentages. Results: Best cut-off for prediction of esophageal varices Grade 1 was platelet count/spleen diameter ratio of 954, which had Specificity of 85.7% and Positive predictive value of 94.1% Cut-off for prediction of Grade 2 esophageal varices was platelet count/spleen diameter ratio of 916 which had a Sensitivity of 78.9%, Specificity of 88.9%. Whereas cut-off for prediction of Grade 3 esophageal varices was a ratio of 899 which had a high Sensitivity of 88% and Negative predictive value of 93.6 % but Specificity was only 64.7% and Positive predictive value of 47.8% only. Conclusions: The platelet count splenic diameter ratio is accurate to be used as screening tool to predict the presence of Grade 2 Esophageal varices in Patients with Cirrhosis. More studies need to be done around the globe for more evidence.